Acute Occlusion of the Infarct-Related Artery as a Predictor of Very Long-Term Mortality in Patients with Acute Myocardial Infarction - Nikola Kos; Ivan Zeljković; Tomislav Krčmar; Karlo Golubić; Fran Šaler; Marijan Erceg; Diana Delić-Brkljačić; Nikola Bulj (Cardiology Research and Practice)
Aim. The survey’s aim was to examine the significance of infarct-related artery (IRA) occlusion (verified angiographically) on very long-term outcomes of patients with acute myocardial infarction, within the STEMI and NSTEMI diagnosis. Methods. A single-center, nonrandomized, registry-based study on patients treated for acute coronary syndrome with percutaneous coronary intervention between June 2011 and December 2016 was conducted. Patients with angiographically proven IRA occlusion (100% stenosis with TIMI flow 0 distal to occlusion) were categorized as occlusive myocardial infarction (OMI) and patients with patent IRA (50–99% stenosis with TIMI 1–3 flow) were categorized as nonocclusive myocardial infarction (NOMI) and very long-term outcomes were analyzed. Data were collected prospectively from the hospital’s PCI registry and the database of the Croatian Institute of Public Health. Results. A total of 2450 patients were included in the study. 796 (32.5%) patients had NOMI and 1654 patients (67.5%) had OMI. According to ECG changes, 1534 patients presented with STEMI (62,6%) and 916 with NSTEMI (37,8%). 88% of STEMI patients presented with OMI and 12% with NOMI, while patients with NSTEMI in 33,8% presented with OMI and in 66,81% with NOMI. A median follow-up was 4.7 years. There was no significant difference in cardiovascular mortality between the groups (14.8% vs 13.1%; OMI vs NOMI, respectively; p=0.374) neither in all-cause mortality (19% vs 21.5%; OMI vs NOMI, respectively; p=0.374). Patients with NSTEMI had a significantly higher very long-term mortality (21.6% vs 18.1%; NSTEMI vs STEMI, respectively; p=0.029). Conclusion. The main findings of the study are as follows: (1) total IRA occlusion was not associated with higher long-term mortality; (2) NSTEMI was associated with a higher mortality rate compared with STEMI, independent of angiographic presentation (OMI/NOMI); (3) IRA occlusion was not associated with significantly higher mortality rates in patients with STEMI and NSTEMI, respectively.